Allele Frequencies of 13 Chromosome X STR in Arab Iraqi Population - Mostafa M. Abdrazik 1,2, Marrib N. Rasheed 1 , Mohammed Mashni Farhan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Short tandem repeat (STR) markers are highly being used for identification of human being in addition topaternity and other forensic cases.The X-chromosome STR (X-STR) markers are a powerful supplementarysystem particularly in deficiency paternity analysis. Several X-linked microsatellites have been assessed butmore studies are necessary to verify the population statistics. In our study, we report allele frequencies of 13X-linked microsatellites (DXS8378, DXS9898, DXS8377, HPRTB, GATA172DO5, DXS7423, DXS6809,DXS7132, DXS101, DXS6789, DXS9902, DXS6807, and DXS7424) in the Iraqi arab population. fiftyBlood samples were collected from healthy unrelated males. A total number of alleles were detected for forall 13 X-STR loci were ( 83 ) and the related frequencies ranging from 0.0200 to 0.5000. Heterozygosityranged from 0.652 to 0.858. Large values were observed, at least 0.999999994, in combined powers ofdiscrimination. The results powerfully suggest that all the X-linked microsatellites defined here can possiblysupport the autosomal systems that used in parentage analysis and different forensic case work.